Effect of nitrogen nutrition and cytokinin spraying on germination components of wheat seed production in terminal heat stress condition - ALI GHATEI; Hamideh Azad; ghasem parmoon (علوم و فناوری بذر ایران)
In order to study germination characteristics of wheat seeds Chamran cultivar of wheat obtained from Plant that treated with different levels of nitrogen and spraying cytokinin under heat stress conditions, this research carried out in factorial experiment in randomized complete design with four replications at seed technology laboratory of Agricultural Sciences and Natural Resources University of Khuzestan. In both conditions Normal (optimum planting date) and Terminal heat stress (late planting date), nitrogen (N) was in four levels (0, 75, 150, and 225 kg.ha-1) and cytokinin (Ck) was in three levels (0, 50 and 100 µM). The results showed the simple effects of N fertilizer on all traits, with the exception of hypocotyl and radicle dry weight, weight vigor index, FMOB, SRUE and thousand grain weight were effective significantly. Effect of planting date was effective significantly on all traits, with the exception of hypocotyl dry weight. The cytokinin (Ck) was effective significantly only on germination percentage, germination uniformity, D90, Length vigor index, SRUE and thousand grain weights. Results of interaction showed treatment of N× planting date had the most Germination rate (0.03 per day). The most mobility of seed reserves (1.6 mg per mg seed) and seed vigor (17.19) was obtained from high levels of N×CK treatment. The effect of N ×Ck× planting showed the most germination (100%) was obtained from high levels of N×Ck treatment and the less germination percentage (66%) was obtained from treatment of late planting date and 150 kg ha-1 N and without cytokinin. so cytokinin increased the resistance of wheat against terminal heat stress and increased germination percentage of seed produced.